Urban planning and real estate development - Ratcliffe, John; Stubbs, Michael, 1962-; Keeping, Miles (New York ; London : Routledge, Taylor & Francis Group, 2021)
"This fourth edition of Urban Planning and Real Estate Development guides readers through the procedural and practical aspects of developing land from the point of view of both planner and developer. The twin processes of planning and property development are inextricably linked - it's not possible to carry out a development strategy without an understanding of the planning process, and equally planners need to know how real estate developers do their job. The planning system is explained, from the increasing emphasis on spatial planning at a national, local and neighbourhood level down to the detailed perspective of the development management process and the specialist requirements of historic buildings and conservation areas. At the same time the authors explain the entire development process from inception through appraisal, valuation and financing to completion. Sustainability and corporate social responsibility and their impact on planning and development are covered in detail, and the future consequences of the Corona-Virus pandemic are explored in new opening and closing chapters setting the text in a global context. Written by a team of authors with many years of academic, professional and research experience, and illustrated throughout with practical case studies and follow-up resources, this book is an invaluable textbook for real estate and planning students, and helps to meet the requirements of the RICS and RTPI Assessment of Professional Competence"--
Revised edition of the authors' Urban planning and real estate development, 2009.
Includes bibliographical references and index.
Keywords: City planning; Real estate development